(untitled) (Journal of Engineering, 2014)
Leaching scheduling techniques are one of the suggested solutions for water scarcity problems .The aim of the study is to show the possibility of using leaching scheduling, when applying the irrigation scheduling program for a certain irrigation project, which was prepare by Water Resources Engineering –University of Baghdad with some modifications to generalized it and it make applicable to various climatic zone and different soil types. The objectives of this research is to build a system that concerns the prediction of the leaching scheduling (depth and date of leaching water), illustrating the main problems (soil salinity, save the amount of leaching requirement, and to maintain crops growth).The other objective is to compare between the calculated amount of leaching water with the amount of water that is suggested by designers. The program includes, the calculating of predicted daily soil salinity ,the depth of leaching water that should be applied to remove the salt from the soil when it reaches a harmful level, and the total annual volume of leaching water. The results showed, that the use of predicted leaching scheduling with its applicable constrains require high attention when choosing the cropping pattern for each climate zone. Also, it was found that the leaching program is a useful tool for saving irrigation water if cropping pattern has been adapted carefully. This means the leaching water depth should be added only when needed, and may not be necessary with each irrigation event.